Effects of waterborne exposure to the antidepressant fluoxetine on swimming, shoaling and anxiety behaviours of the mosquitofish Gambusia holbrooki - Meijide, Fernando Javier (2018)
Chemical pollution from pharmaceuticals is increasingly recognized as a major hazard to the aquatic biota. Among the wide variety of pharmaceuticals, fluoxetine (FLX) is one of the most widely prescribed antidepressants, and therefore, it is frequently identified in the aquatic environment. As FLX is designed to alter human behaviour and many physiological pathways are conserved across vertebrates, this drug may affect the behaviour of fish living in FLX-polluted environments. Here, we exposed groups of female mosquitofish Gambusia holbrooki to waterborne FLX for 14 days, under semi-static conditions with daily renewal of test solutions. Following exposure, we conducted a set of behavioural assays in individual fish, aimed at assessing the effects of FLX on their locomotor activity and behavioural responses. We found that FLX impaired swimming behaviour at high concentrations (25 μg/L and 50 μg/L) but not at low concentrations close to environmental levels (1 μg/L and 5 μg/L). When swimming activity was assessed 5 min after transfer of the focal fish to the testing tank, 50 μg/L FLX was the only concentration showing significant effects. However, when the same trials were performed 24 h later, 25 μg/L FLX turned out to be an effect concentration in addition to 50 μg/L. Interestingly, these concentrations would elicit fish plasma concentrations comprised within the range of human therapeutic doses. When subjected to a light/dark preference test, fish showed tendency to remain less time in the dark area at high FLX concentrations, thus suggesting an anti-anxiety response. Shoaling behaviour was not affected by FLX exposure. Our study contributes to the growing body of literature evaluating the effects of FLX on animal behaviour. Regarding the experimental design used in behavioural testing, our findings suggest that focal fish should be subjected to long habituation periods, namely of at least a few hours, in order to better assess the effects of drug exposure.